2023
DOI: 10.2196/45108
|View full text |Cite
|
Sign up to set email alerts
|

Mpox Panic, Infodemic, and Stigmatization of the Two-Spirit, Lesbian, Gay, Bisexual, Transgender, Queer or Questioning, Intersex, Asexual Community: Geospatial Analysis, Topic Modeling, and Sentiment Analysis of a Large, Multilingual Social Media Database

Abstract: Background The global Mpox (formerly, Monkeypox) outbreak is disproportionately affecting the gay and bisexual men having sex with men community. Objective The aim of this study is to use social media to study country-level variations in topics and sentiments toward Mpox and Two-Spirit, Lesbian, Gay, Bisexual, Transgender, Queer or Questioning, Intersex, Asexual (2SLGBTQIAP+)–related topics. Previous infectious outbreaks have shown that stigma intensifi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 70 publications
0
7
0
1
Order By: Relevance
“…In a generic manner, topic modeling is a methodology that comprises different algorithms that identify, comprehend, and annotate the thematic structure in a collection of documents [77]. Topic modeling of the information on the web has had multiple applications related to the investigation of the perception, preparedness, response, views, and opinions of the general public during different virus outbreaks in the recent past, such as MPox [78], human papillomavirus [79], Zika virus [80], Middle East respiratory syndrome [81], dengue [82], and the flu [83]. In summary, the following research gaps exist in relation to misinformation analysis about COVID-19 on YouTube: (a) A lack of focus on topic modeling: Several works in this field [67][68][69][70][71][72][73][74][75][76] have focused on content analysis of YouTube videos.…”
Section: Review Of Misinformation Analysis On Youtube In the Context ...mentioning
confidence: 99%
“…In a generic manner, topic modeling is a methodology that comprises different algorithms that identify, comprehend, and annotate the thematic structure in a collection of documents [77]. Topic modeling of the information on the web has had multiple applications related to the investigation of the perception, preparedness, response, views, and opinions of the general public during different virus outbreaks in the recent past, such as MPox [78], human papillomavirus [79], Zika virus [80], Middle East respiratory syndrome [81], dengue [82], and the flu [83]. In summary, the following research gaps exist in relation to misinformation analysis about COVID-19 on YouTube: (a) A lack of focus on topic modeling: Several works in this field [67][68][69][70][71][72][73][74][75][76] have focused on content analysis of YouTube videos.…”
Section: Review Of Misinformation Analysis On Youtube In the Context ...mentioning
confidence: 99%
“…Additionally, since TextBlob and VADER were designed mainly for English-language texts, they may not be as effective when used in texts in other languages. Therefore, a toolkit for analyzing text sentiments and emotions in a wide range of languages is the Pysentimiento library, which offers support for multiple languages [20][21][22], including Spanish [23,24]. Furthermore, Pysentimiento uses state-of-the-art machine learning models, such as BERT (Bidirectional Encoder Representations from Transformers) models, for sentiment analysis.…”
Section: Related Workmentioning
confidence: 99%
“…5 Similarly, sexual minority men and gender diverse (SMMGD) individuals have been battling with the so-called “gay disease” stigma attached to HIV/AIDS since the 1980s when the infection and death cases were initially reported in North America to be prevalent among SMMGD. 6 The recent mpox outbreak, coupled with rising misinformation, 7 stigma, 8,9 and conspiracy theories, 10 may, like HIV, experience a stigmatization process that leads to delayed care-seeking and further marginalization of SMMGD individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Even in a study that did focus on mpox and this community, the analyses were performed on mpox tweets containing keywords about lesbian, gay, bisexual, transgender, queer/questioning, intersex and other sexual or gender identities (LGBTQI+), and the posts were from general users not necessarily self-identified as LGBTQI+. 9 Not specific to mpox, one study 12 found more negative patient experience sentiment among LGBTQI+ users than non-LGBTQI+ users, which demonstrates the importance of considering the post author’s identity when analyzing social media data. This study addresses this research gap by analyzing online mpox posts from a specific user cohort, and discussing implications of our findings for health communication tackling mpox and future disease outbreaks with an emphasis on fairness, equity, as well as stigma prevention and control.…”
Section: Introductionmentioning
confidence: 99%